The Influence of Medical Professional Knowledge on Empathy for Pain: Evidence From fNIRS - Xie, Jingdan; Yang, Haibo; Xia, Xiaokai; Yu, Shengyuan (Frontiers in Psychology, 2018)
Empathy is a mental ability that allows one person to understand the mental and emotional state of another and determines how to effectively respond to that person. When a person receives cues that another person is in pain, neural pain circuits within the brain are activated. Studies have shown that compared with non-medical staff, medical practitioners present a lower empathy for pain in medical scenarios, but the mechanism of this phenomenon remains in dispute. This work investigates whether the neural correlates of empathic processes of pain are altered by professional medical knowledge. The participants were 16 medical students who were enrolled at a Chinese medical college and 16 non-medical students who were enrolled at a normal university. Participants were scanned by functional near-infrared spectroscopy (fNIRS) while watching pictures of medical scenarios that were painful or neutral situations. Subjects were asked to evaluate pain intensity supposedly felt by the model in the stimulus displays. And the IRI-C questionnaire was used to measure the empathic ability of participants. The results showed that, there is not significant difference between medical professionals and non-medical professionals subjects in IRI-C questionnaire scores. The subjects of medical professions rated the pain degree of medical pictures significantly lower than those of non-medical professions. The activation areas in non-medical subjects were mainly located in the dorsolateral prefrontal cortex, frontal polar regions, posterior part of the inferior frontal gyrus, supramarginal gyrus, supplementary somatosensory cortex and angular gyrus, whereas there was a wide range of activation in prefrontal lobe region in addition to the somatosensory cortex in medical professionals. These results indicate that the process of pain empathy in medical settings is influenced by medical professional knowledge.